Comparison of ​horace and ​photos Algorithms for Multiphoton Emission in the Context of W Boson Mass Measurement - Ashutosh V. Kotwal; Bodhitha Jayatilaka (Advances in High Energy Physics)
W boson mass measurement is sensitive to QED radiative corrections due to virtual photon loops and real photon emission. The largest shift in the measured mass, which depends on the transverse momentum spectrum of the charged lepton from the boson decay, is caused by the emission of real photons from the final-state lepton. There are a number of calculations and codes available to model the final-state photon emission. We perform a detailed study, comparing the results from horace and photos implementations of the final-state multiphoton emission in the context of a direct measurement of W boson mass at Tevatron. Mass fits are performed using a simulation of the CDF II detector.